2010
DOI: 10.1002/cphc.200901038
|View full text |Cite
|
Sign up to set email alerts
|

On the Compatibility Criteria for Protein Encapsulation inside Mesoporous Materials

Abstract: The properties of the enzyme pepsin, relevant to its incorporation inside the channels of mesoporous silica materials in the preparation of bioinorganic hybrids, are highlighted by molecular dynamics simulations of aqueous solutions of the protein under conditions optimal for encapsulation in SBA-15. The protein size, shape, flexibility and surface properties are calculated with the aim of deriving general accessibility/compatibility criteria favouring encapsulation inside mesoporous systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…The enzyme has optimal activity in the 1-4 pH range, minimal activity above pH 5 and is denatured at pH 6-7 [24,25]. Molecular dynamics simulations on substrate-free pepsin in a pH = 3.6 aqueous solution indicated stability of the enzyme in the medium adopted for the preparation of the pepsin-SBA-15 composite: the active site structure is preserved, relevant residues maintain relative positioning consistent with crystallographic data, and only small fluctuations characterize the pepsin surface charge distribution [26]. Moreover, at the hybrid's fabrication conditions, the average pepsin dimensions amount to approximately 4.5 × 5.0 × 6.6 nm [5,26].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…The enzyme has optimal activity in the 1-4 pH range, minimal activity above pH 5 and is denatured at pH 6-7 [24,25]. Molecular dynamics simulations on substrate-free pepsin in a pH = 3.6 aqueous solution indicated stability of the enzyme in the medium adopted for the preparation of the pepsin-SBA-15 composite: the active site structure is preserved, relevant residues maintain relative positioning consistent with crystallographic data, and only small fluctuations characterize the pepsin surface charge distribution [26]. Moreover, at the hybrid's fabrication conditions, the average pepsin dimensions amount to approximately 4.5 × 5.0 × 6.6 nm [5,26].…”
Section: Introductionmentioning
confidence: 72%
“…Interestingly, owing to the weak surface-protein interaction, the protein shows a significant rotational mobility: indeed, different residues are found in closest contact with the surface along the trajectory and significant variations of the protein orientation are detected. It is to point out that pepsin presents a very complex charge distribution on its surface, with a predominance of negatively charged regions, but also with positively charged patches [26]. The non-uniform charge distribution on pepsin, together with its water-cations-mediated interaction with silica, may therefore explain the absence of a preferred orientation of the enzyme with respect to the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, molecular dynamics simulations showed that, in the presence of Na + and K + cations, a negatively charged peptide (pepsin) solvated by a water droplet can be attracted by a negatively charged silica surface . The peptide‐silica interaction was rationalized thanks to a detailed study of the electrostatic potential of the peptide surface, which exhibited both negative and positive regions . Such model allowed to explain why encapsulation of pepsin in SBA‐15 occurs at pH‐conditions where both protein and mesoporous silica are negatively charged …”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…Immobilization onto inert inorganic materials may cope with stability and compatibility problems, thus favoring advance in technological applications. The success of such a strategy depends on proper selection of the hybrid materials that can support or host the bioactive components while maintaining its activity and selectivity [22] [23]. Some examples of this application are:…”
Section: Porous Materials For a Drug Deliverymentioning
confidence: 99%